Neuroimaging in professional combat sports: consensus statement from the association of ringside physicians - Sethi, N. K.; Neidecker, J. (The Physician and Sportsmedicine, 2023)
Professional boxing, kickboxing, and mixed martial arts (MMA) are popular sports with substantial risk for both acute and chronic traumatic brain injury (TBI). Although rare, combat sports athletes have died in the ring or soon after the completion of a bout. Deaths in these instances are usually the result of an acute catastrophic neurological event such as an acute subdural hematoma (SDH). Other causes may include acute epidural hematoma (EDH), subarachnoid hemorrhage (SAH), intraparenchymal hemorrhage (IPH), or a controversial, rare, and still disputed clinical entity called second-impact syndrome (SIS). Neuroimaging or brain imaging is currently included in the process of registering for a license to compete in combat sports in some jurisdictions of the United States of America and around the world. However, the required imaging specifics and frequency vary with no consensus guidelines. The Association of Ringside Physicians (an international, nonprofit organization dedicated to the health and safety of the combat sports athlete) sets forth this consensus statement to establish neuroimaging guidelines in combat sports. Commissions, ringside physicians, combat sports athletes, trainers, promoters, sanctioning bodies, and other healthcare professionals can use this statement for risk stratification of a professional combat sports athlete prior to licensure, identifying high-risk athletes and for prognostication of the brain health of these athletes over the course of their career. Guidelines are also put forth regarding neuroimaging requirements in the immediate aftermath of a bout.